2010
DOI: 10.1007/s00216-010-4308-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of an analytical protocol for a fast, sensitive and specific protein recognition in paintings by enzyme-linked immunosorbent assay (ELISA)

Abstract: Enzyme-linked immunosorbent assay (ELISA) analysis of proteins offers a particularly promising approach for investigations in cultural heritage on account of its appreciated properties of being highly specific, sensitive, relatively fast, and cost-affordable with respect to other conventional techniques. In spite of that, it has never been fully exploited for routine analyses of painting materials in consideration of several analytical issues that inhibited its diffusion in conservation science: limited sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Therefore, the dilution ratios of 1:3000 for the anti-SF primary antibody and 1:5000 for the secondary were considered to be the optimal antibody dilutions in view of the compromise between high sensitivity and low background. 22 Prior to sample detection, a series of controls, such as positive control (silk fibroin), negative control, BSA and PBS control, were set up to determine the threshold value. In order to ensure the accuracy of the results, the S/N ratio method was employed in this study.…”
Section: Elisamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the dilution ratios of 1:3000 for the anti-SF primary antibody and 1:5000 for the secondary were considered to be the optimal antibody dilutions in view of the compromise between high sensitivity and low background. 22 Prior to sample detection, a series of controls, such as positive control (silk fibroin), negative control, BSA and PBS control, were set up to determine the threshold value. In order to ensure the accuracy of the results, the S/N ratio method was employed in this study.…”
Section: Elisamentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] In recent years, immunological techniques have attracted increasing attention by those working in cultural heritage. For example, milk residues, 18,19 protein-bound materials and organic bones have been detected, [20][21][22][23][24][25] and all of these studies have demonstrated that immunoassays have the potential to identify and localize the proteins in archaeological materials both rapidly and effectively. However, most of the antibodies used in these immunoassays are readily commercially available "off-theshelf", and the need for tailored antibodies for targeted cultural heritages with high sensitivity and specificity is increasingly desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TheC L system showed two orders of magnitude lower LODs than the colorimetric system. [9,11] Our device, which has been developed for on-site application, showed performance similar to those of standard laboratory immunological methods.F urthermore,t he amount of sample (0.5 mg) is similar to the amounts used in other ELISA approaches,which range from 100 mgto1mg. [10] TheL ODs displayed by the CL system were close to those (that is,afew nanograms of target protein) of other ELISA laboratory methods based on fluorescence detection.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…[7] In fact, although originally developed for medicine,i mmunoassays have been used to detect proteins in paintings for over 45 years. [10][11][12] Past research has also confirmed the absence of detectable interferences owing to paint materials. Previous studies have supported the suitability of the immunochemical analyses for aged and historical samples, showing that aging does not hamper recognition of proteins by immunological methods.…”
mentioning
confidence: 86%